Assessment Practice in EFL Classroom: Purpose, Methods and Scoring - Miftahul Farid; Zulfah Fakhruddin; Ambo Dalle (JELITA, 2024)
This research aims to describe teacher purposes, investigate teacher methods, and explain teacher scoring practices in EFL classrooms. The study employs a descriptive quantitative design, collecting data through checklist and observational analyses using Google Forms. The subjects comprise EFL teachers from senior high schools and vocational schools in the Pinrang region. Results reveal that teachers utilize multifaceted assessment practices for interconnected purposes: monitoring student progress, providing feedback, motivating learning, guiding instruction, facilitating differentiation, ensuring accountability, and reporting outcomes transparently. This underscores assessment's vital role in enhancing learning environments and informing teaching decisions. EFL teachers evaluate language proficiency across skills through varied assessments, including instructor-made tests, student tasks, and standardized exams. This approach enables comprehensive insights into students' abilities while addressing individual needs. Scoring practices demonstrate a commitment to fairness, consistency, and comprehensiveness, utilizing rubrics, clear instructions, and balanced evaluation of cognitive, affective, and psychomotor domains. The findings highlight educators' strategic use of assessment purposes and methods to continually improve teaching and learning processes, supporting students' language development. This research contributes to understanding EFL assessment practices in Indonesian secondary education, offering insights for teacher training and educational policy development.